Isolation and Characterization of Arsenic Resistant Pseudomonas Stutzeri ASP3 for its Potential in Arsenic Resistance and Removal - Shakya, Sangita; Pradhan, B. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Inorganic arsenic both arsenite As (III) and arsenate As (V) constitute the highest toxicological risk associated with arsenic in drinking water. Novel methods are in demand for its removal from water, especially in rural areas. For this purpose, the potential of different microbes in arsenic resistance and removal from water has gained interests worldwide. This study investigates the arsenic resistance and removal capacity of a bacterial strain isolated from arsenic enriched water of Rautahat district in Nepal. The concentration of arsenic was by hydride generation atomic absorption spectrophotometer. The isolated bacterium showed high resistance to sodium arsenate up to 4,680.15 mg/l and sodium arsenite up to 649.55 mg/l. The bacterium also conferred multiple heavy metal resistance to zinc chloride (136.28 mg/l), copper sulphate (249.68 mg/l), mercuric chloride (5.43 mg/l) and silver nitrate (3.39 mg/l). The growth rate calculated in the presence of 129.01 mg/l of sodium arsenite was 0.35 h-1 with doubling time of 1.96 h. The strain showed growth in the range of 25–45 °C (optimum 30-35 °C), pH 6 – 9 (optimum 7.5-8.5) and tolerated up to 10% of NaCl. The PCR-based 16S rDNA sequence analysis revealed that the isolated As resistant bacterium is a close relative to P. stutzeri (99%) with 30 hits. The bacterium removed 82.97 % of As (V) and 49.4% of As (III) from culture medium amended with 200 mg/l sodium arsenate and 74.92 mg/l of sodium arsenite respectively.